Perlindungan Hukum Bagi Karyawan Yang Dirugikan Akibat Penahanan Ijazah Oleh Pihak Berwenang Terkait Hak Asasi Manusia - Denis Yusuf Mercury; Agustin Widjiastuti; Paula Paula (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
The company as a place for providing employment, requires accepting workers the detention of the employee's original diploma as a guarantee so that employees cannot violate the rules in the company. Withholding of diplomas is a form of human rights violations that are often ignored by job providers. The purpose of writing this study is to determine the role of the government in handling cases of withholding original diplomas carried out by employers and protecting the human rights of employees to recover original diplomas withheld. The need for legal protection for employees who experience diploma withholding. The research method used by the author in this thesis is using normative research methods with literature research which is research on laws and regulations (Statute Approach) and literature or reading materials and obtained experts and scholars (Conceptual Approach) related to the material discussed. Based on research conducted in the results of the study, there are still many entrepreneurs holding diplomas. Although employers and workers enter into an employment agreement that does not include a clause withholding diplomas, but the original diplomas are still withheld on the basis of mutual trust between employers and employees. The actions of employers have been included in human rights violations, this results in employees not being able to apply for jobs elsewhere that are better in accordance with their abilities. There is a conclusion that there is a legal vacuum, there is no specific law prohibiting the withholding of diplomas.